2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--31008
|View full text |Cite
|
Sign up to set email alerts
|

Student Learning in International Research Programs: A Comparison Across Cultural Contexts

Abstract: is a doctoral candidate in the Department of Engineering Education at Virginia Tech, where she also completed her master's degree in Higher Education. She is the graduate assistant for the Rising Sophomore Abroad Program, a global engineering course and study abroad program for first year engineering students. Her primary research interests are engineering study abroad, developing intercultural competency in engineering students, and international higher education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Although developing global competence is important for engineering students to be successful in the globally connected workforce, many students find it challenging to participate in traditional study abroad programs for financial or scheduling reasons [1]. One type of programming that addresses these concerns is international research experiences, which not only support the development of students' global competencies and technical engineering skills [2], but also provide benefits and opportunities for faculty members who coordinate these experiences. While research has focused on the benefits to students who participate in international research experiences [2]- [6], very little research has examined how the coordination of research experiences for undergraduate and graduate students may benefit faculty members.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although developing global competence is important for engineering students to be successful in the globally connected workforce, many students find it challenging to participate in traditional study abroad programs for financial or scheduling reasons [1]. One type of programming that addresses these concerns is international research experiences, which not only support the development of students' global competencies and technical engineering skills [2], but also provide benefits and opportunities for faculty members who coordinate these experiences. While research has focused on the benefits to students who participate in international research experiences [2]- [6], very little research has examined how the coordination of research experiences for undergraduate and graduate students may benefit faculty members.…”
Section: Introductionmentioning
confidence: 99%
“…One type of programming that addresses these concerns is international research experiences, which not only support the development of students' global competencies and technical engineering skills [2], but also provide benefits and opportunities for faculty members who coordinate these experiences. While research has focused on the benefits to students who participate in international research experiences [2]- [6], very little research has examined how the coordination of research experiences for undergraduate and graduate students may benefit faculty members. Faculty involvement has been highlighted as an important factor in encouraging student participation in international programs, and research experiences have been highlighted as an important option to consider for both faculty and students in STEM disciplines [7].…”
Section: Introductionmentioning
confidence: 99%
“…One way to develop researchers who are both interculturally competent and able to navigate global research networks within their field is to provide international research experiences for students. Prior work has indicated that such experiences lead to a wide range of learning outcomes including intercultural competence, research skills, personal development, and, importantly, a new perspective on their career goals and trajectory [1]- [6]. However, in the midst of the COVID-19 pandemic, international collaborations and programs for students faced challenges in continuing their typical operations.…”
mentioning
confidence: 99%